Evaluating the Accuracy of Tempromandibular Joint Panoramic Radiography in Condylar Positioning - Seyed Hossein Hoseini Zarch; Adineh Javadian Langrodi; Lida Bahramian; Fereshteh Jahed Kihani; Abdollah Javan (Mashhad University of Medical Sciences, 2017)
Introduction: Panoramic radiography is a diagnostic tool, which has a widespread application in the assessment of tempromandibular joint (TMJ) by the dentists as well as ear, nose, and throat specialists. Regarding this, the present study aimed to compare the accuracy of this method in the evaluation of the condylar position and osseous changes with that of the cone beam computed tomography (CBCT) as the gold standard method. Materials & Methods: This study was conducted on 28 patients with both TMJ panoramic imaging and bilateral CBCT imaging of TMJs. The condylar position was determined in closed-mouth and maximum intercuspation positions based on the measurement of superior, posterior, and anterior joint spaces and osseous changes of condyle, including erosions, osteophytes, resorbtion, Ely's cyst, flattening, and sclerosis. The images were evaluated by two expert maxillofacial radiologists. Finally, the accuracy of TMJ panoramic radiography was compared with that of CBCT in terms of the sensitivity, specificity, as well as positive and negative predictive values. Results: According to the results, there was a significant difference between the two techniques regarding the diagnosis of anterior and posterior condylar positions in horizontal dimension (P=0.012, P=0.007). The sensitivity rates in the anterior and posterior positions were 50% and 51%, and the specificity rates were 55% and 55%, respectively. Regarding the identification of condylar position in vertical dimension, the two methods showed a significant difference only in the narrowing of superior joint space (P=0.004). The sensitivity and specificity in the narrowing of superior joint space in the vertical dimension were 100% and 79%, respectively. Regarding the osseous changes, the TMJ panoramic method had a poorer performance in the diagnosis of erosion (sensitivity: 29%, specificity: 95%), compared to the CBCT. Nevertheless, no significant difference was observed between the two methods regarding the diagnosis of osteophytes and flattening. Conclusion: TMJ panoramic radiography had a lot of limitations in the detection of the condylar position both in horizontal and vertical dimensions, compared to the CBCT. However, panoramic radiography can be relatively helpful in the initial screening of osseous changes for determining the healthy cases.